2020
DOI: 10.21608/fsrt.2020.23438.1009
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 and GCKR Gene Polymorphisms influence genetic Susceptibility to NAFLD in Obese Egyptians

Abstract: Environmental and genetic factors have a crucial role in the development and progression of non-alcoholic fatty liver disease (NAFLD). The aim of the present study is to investigate the association between single nucleotide polymorphism (SNP) rs738409 in PNPLA3 gene and rs1260326 in GCKR gene and the development of NAFLD in obese Egyptian population. Forty obese subjects (20 with NAFLD and 20 without NAFLD) and 20 control subjects were enrolled in this study. All subjects were genotyped for (rs738409) PNPLA3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Yuan et al observed an increase in TG levels of rs1260326-T carriers and demonstrated an association between GCKR rs1260326-T and fatty liver by studying the elderly Chinese Han population [ 72 ]. Furthermore, Nahass et al confirmed that GCKR rs1260326 allele T was associated with susceptibility to NAFLD [ 83 ]. Another GCKR gene variant, rs780094, is reported to increase triglyceride levels in the Chinese population [ 46 ].…”
Section: Metabolic-related Genes Influencing Nafldmentioning
confidence: 99%
“…Yuan et al observed an increase in TG levels of rs1260326-T carriers and demonstrated an association between GCKR rs1260326-T and fatty liver by studying the elderly Chinese Han population [ 72 ]. Furthermore, Nahass et al confirmed that GCKR rs1260326 allele T was associated with susceptibility to NAFLD [ 83 ]. Another GCKR gene variant, rs780094, is reported to increase triglyceride levels in the Chinese population [ 46 ].…”
Section: Metabolic-related Genes Influencing Nafldmentioning
confidence: 99%